ANALISIS PENGARUH CADANGAN DEVISA, PEMBAYARAN UTANG LUAR NEGERI, POSISI UTANG LUAR NEGERI DAN BI RATE TERHADAP MONEY SUPPLY DI INDONESIA - Silfia; Budi Marwoto, Pan; Prima Nugroho, Stefanus (Jurnal Akuntansi Bisnis Dan Keuangan, 2018)
The purpose of this study is to prove and verify whether the effect of the Foreign Exchange Reserves, the Payment of Foreign Debt, the Position of Foreign Debt, and the BI Rate influence significantly towards the Money Supply in Indonesia. The data used in this study was secondary data (in the form of time series data). The time series data in this study was used from 2007 to 2016 taken from Badan Pusat Statistik. Processing techniques and data analysis in this study used Multiple Linear Regression Analyses and hypothesis testing. Hypothesis testing uses t-test and F-test with 5% significance level. This study also used the Coefficient of Determination (R2) to determine the ability of independent variables on explaining the dependent Variables. The result of the Linear Regression Equation of this research is MS = -171010,2 - 12,90985 CD + 24,29496 Pemb UL + 21,47621 Pos UL - 97241,7 BR. The result of the simultaneous hypothesis test (F-test) showed that Foreign Exchange Reserves, the Payment of Foreign Debt, the Position of Foreign Debt, and the BI Rate simultaneously affect the Money Supply in Indonesia. The result of the partial hypothesis test showed that Payment of Foreign Debt and the Position of Foreign Debt negatively affect the Money Supply in Indonesia. The value of the Coefficient of Determination (R2) of 0,994941, this value can be defined that 99,4941% of Indonesia’s Money Supply can be explained by the Foreign Exchange Reserves, the Payment of Foreign Debt, the Position of Foreign Debt, and the BI Rate. While the remaining 0,5059% is explained by other factors outside this study.